AN ANALYSIS OF STUDENTS’ ABILITY AND PROBLEM IN WRITING ANALYTICAL EXPOSITION TEXT - Fanalisa Elfa (INOVISH JOURNAL, 2020)
Abstract This research aims to analyze the ability and problem of students in writing analytical exposition text. The participants of this research were the students at XI IPA 2 SMAN I Ulakan Tapakis. The type of this research was descriptive research.  The data of the research was collected by administering writing task. The data collected were analyzed by using quantitative and qualitative analysis. The finding shows that the ability of students in writing thesis arguments, reiteration, language features (Simple present, passive voice and conjunction), vocabulary and mechanics was unsatisfactory. Furthermore they had some problems in writing thesis arguments, reiteration, language features (Simple present, passive voice and conjunction), vocabulary and mechanics. From the data gotten, it can be concluded that the students had unsatisfactory performance in writing analytical exposition text. Key words: students’ability, students’ problems, analytical exposition text.